Simplify:

-( (a^2) / (b^3) )^3 (-a^2 b^2)^3

= -( a^6 / b^9) (-a^6 b^6)

= -a^6 * -a^6 * b^(6-9)

= a^12 * b^-3

Did I simplify this correctly? The difficult part is the -(a^6) and (-a^6).

Thanks.

Printable View

- Oct 9th 2006, 07:02 PMshentonSimplification problem
Simplify:

-( (a^2) / (b^3) )^3 (-a^2 b^2)^3

= -( a^6 / b^9) (-a^6 b^6)

= -a^6 * -a^6 * b^(6-9)

= a^12 * b^-3

Did I simplify this correctly? The difficult part is the -(a^6) and (-a^6).

Thanks. - Oct 9th 2006, 07:08 PMtopsquark
The two expressions -(a^6) and (-a^6) are the same. The ones you need to worry about are -(a^6) and (-a)^6.

Since the red negative sign doesn't show up in any parenthesis it is simply a constant factor out in front of everything. For the black negative sign think of it this way:

(-a^2 b^2)^3 = (-1)^3 * (a^2)^3 * (b^2)^3 = -(a^2)^3 * (b^2)^3

which is again outside of everything. So you got it right. :)

-Dan - Oct 9th 2006, 07:25 PMshenton
Thanks, topsquark for the help and advise. :)